Tracking Malay Vocabulary: Data in Pigafetta's Dictionary (1521) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
This article studies the oldest Malay dictionary based on data collected by Antonio Pigafetta in 1521. This dictionary, which was organized by Pigafetta himself (1522-1524) and published in part in 1536, survives in the Ambrosiana manuscript in Milan, Italy (Robertson 1906). Only a few 20th-century scholars have studied these lexical data. However, for various reasons, the identification of the meanings and sources of these lexical items has not been adequately explored. At the present time, 500 years after Pigafetta's fieldwork, new materials are available and can be utilized. This article examines some of the data in Pigafetta's dictionary in order to understand the sociolinguistic setting in East Nusantara at that time as well as to trace the meanings and sources of the 1521 data.Full text: PDF